Implications for Tumor Microenvironment and Epithelial Crosstalk in the Management of Gastrointestinal Cancers. (31st October 2019) - Ge, Yang; Westphalen, C. Benedikt; Ma, Wen Wee; Vega, Kenneth J.; Weygant, Nathaniel
Abstract : Rapid advances in technology are revealing previously unknown organization, cooperation, and limitations within the population of nontumor cells surrounding the tumor epithelium known as the tumor microenvironment (TME). Nowhere are these findings more pertinent than in the gastrointestinal (GI) tract where exquisite cell specialization supports a complex microenvironmental niche characterized by rapid stemness-associated cell turnover, pathogen sensing, epithelial orchestration of immune signaling, and other facets that maintain the complex balance between homeostasis, inflammation, and disease. Here, we summarize and discuss select emerging concepts in the precancerous microenvironment, TME, and tumor epithelial-TME crosstalk as well as their implications for the management of GI cancers.